PEMBELAJAR INOVATIF MENGHANTAR TERCAPAINYA ORIENTASI PENCAPAIAN AKADEMIK DAN ORIENTASI PERKEMBANGAN MANUSIAWI - Elias Anwar (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2021)
A school is required to meet educational standards which include academic excellence, accreditation, a good curriculum, competent or professional teachers, effective educational technology, high graduation rates. In addition to high academic demands, schools must also be able to meet the standards of human development. So there are two orientations in education, namely the orientation of academic achievement and the orientation of human development. In short, it can be said that the orientation of academic achievement is obtaining graduation in the highest ranking nationally and even internationally, being able to master science and being able to enter well-known universities. Indeed, education on the one hand is required to achieve superior academic achievement (first orientation), on the other hand education must also help students achieve human development (second orientation). So one alternative in bridging the two orientations, teaching staff need to recognize and innovate learning in order to be able to deliver students with creative methods that also bring the humanities spirit in education itself.